Aggressive tax avoidance determinant factors of cg rankings 100 public companies by Indonesian institute for corporate directorship / Ani Kusbandiyah, Norlia Mat Norwani and Mohd Abdullah Jusoh. - Kusbandiyah, Ani; Mat Norwani, Norlia; Jusoh, Mohd Abdullah (Universiti Teknologi Mara Selangor, 2020)
This research aims to obtain empirical evidence of whether there is influence family ownership, foreign ownership, corporate governance, permanent different and temporary different of aggressive tax avoidance. Research data are secondary data form of financial statements information 100 CG rankings of public companies by Indonesian Institute for Corporate Directorship. period 2013 – 2016. The results of this study concluded that foreign, family ownership, and permanent different negatively influence toward, aggressive tax avoidance, but corporate governance and temporary different no influence toward aggressive tax avoidance. The results of this research at showed from Sig value of foreign ownership 0.014 less than 0.05, family ownership 0.22 less than 0.05, permanent different 0.60 less than 0.10. But sig value of corporate governance 0.405 more than 0.05 and temporary different 0.289 more than 0.05.